2009
DOI: 10.1111/j.1365-2613.2009.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, cell proliferation and modulation of cyclin‐dependent kinase inhibitor p21cip1 in vascular remodelling during vein arterialization in the rat

Abstract: Neo-intima development and atherosclerosis limit long-term vein graft use for revascularization of ischaemic tissues. Using a rat model, which is technically less challenging than smaller rodents, we provide evidence that the temporal morphological, cellular, and key molecular events during vein arterialization resemble the human vein graft adaptation. Right jugular vein was surgically connected to carotid artery and observed up to 90 days. Morphometry demonstrated gradual thickening of the medial layer and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
14
0
4
Order By: Relevance
“…INK4a remains unchanged during rat vein arterialization 24) . Cardenas et al demonstrated that the rate of venous thrombosis is increased in vascular injury models of p16…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…INK4a remains unchanged during rat vein arterialization 24) . Cardenas et al demonstrated that the rate of venous thrombosis is increased in vascular injury models of p16…”
Section: Discussionmentioning
confidence: 86%
“…Cell proliferation is required for the arterial-vein graft to adjust to new hemodynamic conditions. However, an uncontrolled proliferative process can result in the occlusion of the vein graft or the development of atherosclerotic lesions 24) . Borin et al reported that p21 is the main CKI, while the level of p16…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations